TATYANAITE, A NEW PLATINUM-GROUP MINERAL, THE PT ANALOGUE OF TAIMYRITE, FROM THE NORIL'SK COMPLEX (NORTHERN SIBERIA, RUSSIA) - Barkov A.Y.; Martin R.F.; Poirier G.; Tarkian M.; Pakhomovskii Y.A.; Men'shikov Y.P. (My University, 2000)
Tatyanaite, a new mineral from Noril'sk (Siberia), is the Pt analogue of taimyrite. It is defined as the member(s) of the tatyanaite-taimyrite solid-solution series with Pt > Pd. Tatyanaite solid solution occurs in massive sulphide ore, which consists of chalcopyrite and subordinate pentlandite, pyrrhotite, and cubanite (or isocubanite). It occurs as central zones of large, elongate grains (up to ~1 mm) and as aggregates of smaller grains associated with Ag-Au alloys. The associated minerals include unusually Pt-rich taimyrite [(Pd1.25Pt0.86)(Cu0.85Ni(<0.01)(Sn1.01Sb0.02)], atokite-rustenburgite, paolovite, froodite, sperrylite, maslovite, and galena. Cryptic zoning (Pt increases and Pd decreases toward the centre) and polysynthetic twins are characteristic. In reflected light, tatyanaite is pink with lilac tinge in air. Bireflectance is weak to distinct, from brownish pink to pinkish lilac. Anisotropy is distinct to moderate, from light brown to dark blue. Reflectance percentages in air and (in oil) are, for R1 and R2, 470 nm 42.8, 44.1 (32.8, 33.3), 546 nm 49.5, 50.0 (37.6, 38.8), 589 nm 51.8, 54.6 (38.9, 39.9), and 650 nm 55.6, 56.8 (41.6, 44.2). It is ductile; the microhardness is VHN20 = 292-348, mean of 327 kg/mm2. The average of nine electron-microprobe analyses gave Pt 45.38, Pd 19.53, Cu 10.62, Ni 0.15, Fe 0.03, Sn 23.02, Sb 0.27, sum 99.0 wt.%, corresponding to [(Pt4.76Pd3.75)(Σ8.51)Cu0.48](Σ8.99)(Cu2.94Ni0.05Fe0.01)(Σ3.00)(Sn3.96Sb0.05)(Σ4.01) [or to (Pt1.19Pd0.94)(Cu0.85Ni0.01Fe(<0.01)) (Sn0.99 Sb0.01)]. The powder pattern is similar to that of synthetic Pd9Cu3Sn4, and, by analogy with the latter, it was indexed for an orthorhombic cell with a = 7.89(1) Å, b = 4.07(1) Å and c = 7.73(1) Å, and V = 248(1) Å3. The three strongest lines in the pattern are 2.283 (10,212), 2.163 (4,203) and 1.369 (3,323). Tatyanaite-taimyrite formed from a late-stage liquid rich in noble metals, Cu and Sn.